PEMANFAATAN TEKNIK VIDEOGRAFI UNTUK PEMODELAN ARUS LALU LINTAS (Studi Kasus : Jalan Veteran, Kota Serang, Provinsi Banten) - , CENDEKIA IVANNA F ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The traffic flow problem at Jalan Veteran, Serang, Banten province, caused by an increase of population. These problem resulted in increasing in the number of the private vehicles manufacturers demand. Traffic flow that are more dense causing many negative impact felt by society including the traffic jam, air pollution, increasing number of accidents and increased travel time. Therefore we need a way to overcome the traffic flow problems. One way is by improving traffic flow system by indentifying of daily oncoming vehicles information. Manual traffic flow measurement involves many time and cost. The process of traffic flow data and data measurement also required a lot of teams. Therefore, solution is needed to solve these problem. Videography technique are expected to help provide information by recording the traffic flow state. This technique has adventages, including cost considerations, more efficient, data processing become easier and can providing continous data. This study aims to determine the number of vehicles passing Jalan Veteran, Serang, Banten province in a week using videography technique and modeling the Jalan Veteran, Serang, Banten province traffic flow with image sequence. For recording purposes, the model required the recording of traffic flow in Jalan Veteran, Serang, Banten province for one week as research material. After prepared the technical plans, including tools and materials research, data acquisition, recording traffic flow, field sketch and placement of ground control points. The results of this work is the data acquisition can be obtained by determining the schedule for one week of data collection, recording of the traffic generating traffic video by installing a video recording device at cross bridge. And the videos are converted using Free FLV Converter V.7.5.0 software from (*.mov) to (*.avi). which is then used to calculate the flow of traffic and generate traffic count. The next stage is cutting the video into the video frames that will be made for model the traffic flow with image sequences. Besides the traffic flow data, image sequences provide the highest and lowest visual information state of traffic flow in Jalan Veteran, Serang, Banten Province. From these results we can conclude the value of the highest traffic flow in Jalan Veteran, Serang - Banten there on Tuesday morning at 07:00 to 07:30 with the number of vehicles by 2,933 vehicles / hour. For the lowest number of traffic flows on Friday morning at 12:00 to 12:30 with the number of vehicle for 817 vehicles / hour.